"Dublety warszawskie" - Archiwum Biblioteki Kórnickiej (1869-1923); Bank Włościański Poznań; Biblioteka Kórnicka; Biblioteka Ordynacji Zamojskiej Warszawa; Flinsch Ferdinand, |Fabrik-Papierlager Berlin; Rosenthal's Ludwig |Antiquariat Monachium; Żupański Jan Konstanty, |Księgarnia Poznań (1899)
Bank Włościański w Poznaniu, 1904, k. 47. - Flinsch Ferd., Berlin, 1899, k. 1-2. - Jolowicz Józef, 1903, (2), k. 23-24. - Korzon Tadeusz (Biblioteka Ordynacji Zamojskiej w Warszawie), 1899-1904, (17), k. 3-22, 34-41, 48-49, w tym list do Księgarni J. K. Żupańskiego w Poznaniu, 1902, k. 19-20. -
1000,00
Keywords: Berlin; Fabrik-Papierlager - Flinsch Ferdinand; Monachium; księgarnia - Rosenthal Ludwig; Poznań; księgarnia - Jolowicz Józef; Bank Włościański; księgarnia - Żupański Jan Konstanty; Drukarnia "Dziennika Poznańskiego"; Warszawa; Biblioteka Ordynacji Zamojskiej; Korespondencja; Księgarnie